Diversity of Asteroidea on Gili Ketapang Beach Probolinggo Regency and Its Use as Popular Scientific Book - Buyami Buyami; Suratno Suratno; Jekti Prihatin (Pancaran Pendidikan, 2020)
Popular scientific books are books that adhere to scientific standards and are displayed in common language and attractive layouts so that the public is more interested in reading them Starfish (Asteroidea) is an animal that plays an important role in the coastal environment, namely as the bioindicator of the water's contamination. One of the pristine waters of the beach and has a high enough biological richness is Gili Ketapang, Probolinggo beach. This research aims to determine the level of diversity of Asteroidea in Gili Ketapang beach, Probolinggo. This research is a type of quantitative descriptive research with the method of Transect plotting. The results of this study found 2 types of Asteroidea with a total of 100 individuals. Asteroidea is found in 1 family, 1 genus and 2 types of Asteroideans. The type of Asteroidea is a family of Archasteridae, a genus of Archaster and the type of Archaster typicus and Archaster angulatus. The value of the diversity index of Asteroidea in Gili Beach Ketapang Regency of Probolinggo is 1.323